2021
DOI: 10.1016/j.puhe.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Just a bad flu? Tackling the “infodemic” in Ireland through a comparative analysis of hospitalised cases of COVID-19 and influenza

Abstract: Objectives COVID-19 infection has been compared to seasonal influenza as an argument against non-pharmacological population based infection control measures known as “lockdowns”. Our study sought to compare disease severity measures for patients in Ireland hospitalised with COVID-19 against those hospitalised with seasonal influenza. Study Design Retrospective population-based cohort study. Methods COVID-19 hospital episodes and seasonal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…16 The pandemic was similarly described by authors in several other countries, including China, 17 Africa, 18 South Korea, 19 and Ireland. 20 The high media-dependency for rapid dissemination of current data and research on COVID-19 information that emerged during the pandemic only exacerbated the infodemic, 21 as people were hoping to learn from quick information sources in a rush to obtain substantive data and research about COVID-19. Traditional mass media, such as television, newspapers, and websites, provided an abundance of pandemic-related information, and many people relied on the news for reliable information, especially if they were of the low-income category.…”
Section: Discussionmentioning
confidence: 99%
“…16 The pandemic was similarly described by authors in several other countries, including China, 17 Africa, 18 South Korea, 19 and Ireland. 20 The high media-dependency for rapid dissemination of current data and research on COVID-19 information that emerged during the pandemic only exacerbated the infodemic, 21 as people were hoping to learn from quick information sources in a rush to obtain substantive data and research about COVID-19. Traditional mass media, such as television, newspapers, and websites, provided an abundance of pandemic-related information, and many people relied on the news for reliable information, especially if they were of the low-income category.…”
Section: Discussionmentioning
confidence: 99%
“…Sebuah riset di Irlandia menunjukkan bahwa infodemic telah mengancam proses penanganan Covid-19 mulai dari sisi kebijakan kesehatan hingga kepercayaan publik pada institusi kesehatan. Infodemic juga berkali-kali diungkapkan oleh World Health Organization (WHO) sebagai salah satu permasalahan baru yang harus dihadapi di saat penyebaran virus Covid-19 (Beatty et al, 2021).…”
Section: Pandemiunclassified
“…With most of both populations having a neutral response or believing they are less likely to contract COVID-19 compared to others, it could be because they perform good practices towards COVID-19 and believe that they can protect themselves [11]. A study carried out by Beatty et al [25] observed that 81.3% of respondents were under the impression that COVID-19 is more severe than the flu. The authors measured the severity and impact of COVID-19 from the healthcare sector and compared the statistics to hospitalisations from influenza.…”
Section: Risk Perceptionsmentioning
confidence: 99%